The synthesis of urethane acrylate resin from palm fatty acid distillate and some mechanical properties / Teo Kim Teck - Teo , Kim Teck (2020)
Depletion of petroleum reserves and increasing environmental concerns have stimulated the efforts to explore materials from readily available, renewable natural resources, such as carbohydrates, oils, fats and proteins. Plant oil and its fatty acids are promising renewable resources to produce environmentally friendly polymeric materials. Palm oil is a major crop in Malaysia and consequently palm fatty acid distillate (PFAD) has been an abundant by-product during the refinery process. PFAD could be a renewable raw material for industrial application. Thus, we develop new PFAD-based acrylate resins UV curable for coatings applications. The resins could be produced by two approaches. Firstly, mixtures of varying amount of PFAD, isophthalic acid, phthalic anhydride, neopentyl glycol and pentaerythritol were reacted to produce hydroxyl terminated macromers. Five macromers with 15, 25, 45, 55 and 70% of PFAD were synthesized. Each macromer was reacted with toluene diisocyanate and 2-hydroxyl ethyl acrylate to produce a UV curable urethane acrylate resin. The content of PFAD has significant influence on the final UV cured film. The urethane acrylate resins with 15–55% PFAD in the macromers, could be UV-cured to form hard films with a Tg of 35–62°C. These resins have potential application for wood coatings. However, urethane acrylate resin with 70% PFAD, cured to form a soft film with Tg < 30°C and not useful for coating application. In particular, at around 45% PFAD, the resin could be UV-cured in 60 s to film that has achieved pendulum hardness of 107 s and Tg of 54C. In the second approach, the influence of different polybasic acids in PFAD-based urethane acrylate resin synthesis was studied. A series of PFAD urethane acrylate resins were synthesized, fixing the PFAD at 45%, and using isophthalic acid (IPA), terephthalic acid (TPA), phthalic anhydride (PA) and adipic acid (AA) as polybasic acid building block. All macromers were formulated with same hydroxyl value at 91 mgKOH/g and polybasic acid equivalent of 0.32 g/mol in 100 g of resin. The results showed that the different structure of polybasic acid has affected the performance of urethane acrylate resin. Generally, aromatic type of polybasic acid can produce higher Tg and hardness of UV cured film. Outstanding mechanical and physical properties such as adhesion, solvent, water, corrosion resistant can be achieved by using aromatic diacids in metal coating application. To a certain extent, good weathering resistance can be achieved on metal coating. Aliphatic type of diacid could impart good flexibility and soft film formation on the PFAD urethane acrylate UV cured film.